Five year recall study of Sri Lnkan women with previous pregnancy induced hypertension - Arandara, D.C.; Arasalingam, A.; Wijeratne, V.; Wijeyaratne, C.N.; Seneviratne, H.R. (Sri Lanka College of Obstetricians and Gynecologist, 2005)
Arandara, D. C., Arasalingam, A., Wijeratne, V., Wijeyaratne, C. N., & Seneviratne, H. R. (2005). Five year recall study of Sri Lnkan women with previous pregnancy induced hypertension.
Keywords: PREGNANCY INDUCED HYPERTENSION